PENERAPAN PEMBELAJARAN KOOPERATIF MODEL NUMBER HEAD TOGETHER (NHT) DENGAN MEDIA KOKAMI DALAM MENINGKATKAN HASIL BELAJAR IPS TERPADU KOMPETENSI DASAR MENGIDENTIFIKASI TINDAKAN EKONOMI BERDASARKAN MOTIF DAN PRINSIP EKONOMI DALAM BERBAGAI KEGIATAN SEHARI-HAR - Dassucik Dassucik (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2017)
There are various distinct issues in the learning process. One problem that often occurs in the classroom is the low mastery learning students due to low student learning outcomes. One is the science subjects of class VII. at SMP Negeri 2 Situbondo. The purpose of this study was to determine the yield increase by applying Student Model Number Head Together (NHT) Seventh Grade Science Lesson In SMP Negeri 2 Situbondo. The approach used in this research is a qualitative approach, while type of research is a classroom action research with research subjects were students of class VII at SMP Negeri 2 Situbondo. The data obtained were collected by the method of observation, interviews, and documentation, while the implementation. Based on the results of the analysis can be seen that NHT learning can increase academic skills and can enhance cooperation among students, because the NHT learning students can find their own concepts that should be known by the investigation of real problems. In the first cycle is complete learn classical by 82% and the individual students who completed as many as 23 students and 5 students not complete. Factors - factors that cause incomplete study of 5 students is that they did not master the material, less conscientious, shy to ask, and less good at set time in doing it. In the second cycle was reached in the classical mastery learning students by 86% as many as 24 students who completed individually.